Language and decision making: Board members and the investment in the future - Florian Rottner (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2021)
Recent research has shown that the grammatical representation of the future in languages influences how future-oriented an individual behaves in her private life. In this paper, I examine whether this effect of language characteristics on a person's behaviour is also evident in the business world. I test the hypothesis that companies with board members whose native language grammatically separates the present from the future are less future-oriented. I find significant effects of the inflectional marking of the future in one language on the growth rate of a company's intangible assets, which I use as a benchmark for its future orientation.
Keywords: O10; O30; Z13; 330; Language Structure; Future Tense; Research and Development Activities